2020
DOI: 10.1021/acs.inorgchem.0c00233
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide-Bridged Fe-Co Polynuclear Clusters Based on Four-Coordinate Cobalt(II)

Abstract: Treatment of CoCl 2 •6H 2 O and tris(pyrazolyl-1-yl)borate tricyanoiron(III) anions at 55 °C afforded a series of new Fe-Co polynuclear clusters: {Co 2 Cl 2 (DMF) 4 [(Tp 4-Me )Fe(CN) 3 ] 2 } (1; Tp 4-Me = hydridotris(4methylpyrazol-1-yl)borate), (H 3 O + )@{Co 4 Cl 4 [(Tp 4-Me )Fe(CN) 3 ] 4 } (2), (MePh 3 P) 4 {Co 6 Cl 6 [(Tp 4-Me )Fe(CN) 3 ] 6 }•15CH 3 CN•3CH 3 OH•2H 2 O (3), and (BnEt 3 N) 4 {Co 5 Cl 8 [(Tp*)Fe(CN) 3 ] 4 }•4CH 3 CN•2H 2 O (4; Tp*= hydridotris(3,5dimethylpyrazol-1-yl)borate). They feature an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…The obtained J values further confirm the ferromagnetic coupling between Fe III –Ni II and Ni II –Ni II ions, suggesting an S T = 3 ground spin state. All of the fitting results are comparable to those reported for cyanide-bridged Fe III –Ni II complexes containing [(Tp R )­Fe­(CN) 3 ] − units and azide-bridged Ni­(II) complexes. Accordingly, using an S T = 3 macro-spin model with the following spin Hamiltonian (eq ), the magnetization data were fitted with the PHI program to extract the axial and transverse ( E ) zfs parameters of the entire molecule (Figure S13): …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The obtained J values further confirm the ferromagnetic coupling between Fe III –Ni II and Ni II –Ni II ions, suggesting an S T = 3 ground spin state. All of the fitting results are comparable to those reported for cyanide-bridged Fe III –Ni II complexes containing [(Tp R )­Fe­(CN) 3 ] − units and azide-bridged Ni­(II) complexes. Accordingly, using an S T = 3 macro-spin model with the following spin Hamiltonian (eq ), the magnetization data were fitted with the PHI program to extract the axial and transverse ( E ) zfs parameters of the entire molecule (Figure S13): …”
Section: Resultssupporting
confidence: 69%
“…Moreover, the [(Tp R )­Fe­(CN) 3 ] − anions have also been widely used for constructing charge transfer systems because the electronic properties of the building block can be systematically modified through chemical modification . Self-assembly of these anions with either fully solvated metallic salts [M II (sol) n ] 2+ or partly coordinated [(L)­M­(sol) m ] 2+ units (L = chelate ligand) afforded a series of low-dimensional complexes, such as dinuclear complexes, squares, cubes, and one-dimensional (1D) chains with fascinating magnetic properties . Remarkably, the realization of good alignments (colinear or parallel) of the B···Fe vectors in these structures may help contribute to the SMM behavior, as evidenced in a series of Fe–Ni complexes ([Fe III 2 Ni II ], [Fe III 4 Ni II 2 ], and [Fe III 6 Ni II 3 ]) with a general motif of [Fe 2 Ni] n (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the primary difference in structure between 1 and 2 ( 3 ) can be explained by the charge density match. , The more highly negatively charged [SiW 12 O 40 ] 4– will facilitate the formation of the more positively charged {Fe 2 M 3 } n chain species (+4 per unit) rather than the {Fe 2 M 2 } square species (+2 per unit). It should be mentioned that the use of triflate instead of chloride salts may avoid the formation of the asymmetric square complex {Co 2 Cl 2 (DMF) 4 [(Tp 4‑Me )­Fe­(CN) 3 ] 2 } (Tp 4‑Me = hydridotris­(4-methylpyrazol-1-yl)­borate) reported previously by us . A TGA analysis revealed that the sample of 1 desolvated and decomposed easily with a continuous weight loss above room temperature, while those of 2 and 3 showed a relatively stable plateau before a quick weight loss of 8.4–9.9% at around 120 °C, significantly greater than the calculated value (4.5%) for the lattice DMF molecules, indicating that part of the coordinating DMF molecules are lost in this process (Figures S1–S3).…”
Section: Resultsmentioning
confidence: 89%
“…However, very limited success has been achieved in introducing POMs into the cyanometalate system. We presumed that these highly negatively charged species might facilitate the generation of highly positively charged {Fe–CN–M} moieties as counteranions from the perspective of charge density matching . In addition, these diamagnetic nanosized POMs will necessarily result in the good separation of the individual molecules, an important aspect for reducing the intermolecular interaction .…”
Section: Introductionmentioning
confidence: 99%
“…With long-standing interest in the switchable materials based on [(Tp R )Fe(CN) 3 ] − (Tp R = poly(pyrazol-1yl)borate) building blocks,[37][38][39][40] we recently turned our interest in a series of {Fe III Fe II } complexes for better understanding this encrypted system. Herein, we prepared two new cubic mixed-valence {FeIII …”
mentioning
confidence: 99%